Biomechanical analysis of printable functionally graded material (FGM) dental implants for different bone densities. (November 2022) - Ouldyerou, Abdelhak; Mehboob, Hassan; Merdji, Ali; Aminallah, Laid; Mehboob, Ali; Mukdadi, Osama M.
Abstract: The long-term success of a dental implant is related to the material and design of the implant, and bone density. Conventional implants cause stress-shielding due to a mismatch between the implant and bone stiffness. Functionally graded porous materials and designs are a great choice for the design of implants to control the local stiffness at a certain location to meet the biomechanical requirements. The purpose of this study is to analyze five designs of axial and radial functionally graded materials (FGM) implants besides the conventional implant and conical and cylindrical shapes that were simulated with five different bone densities. The results showed that strain in bone increased with a decrease in cancellous bone density. The shape of the implant did not play an important role in strain/stress distribution. Conventional implants showed optimal strain (1000–2240 με) in low-density (0.7–0.8 g/cm 3 ) bone, however, FGM implants produced optimal strain (990–1280 με) in the high-density bone (0.9–1 g/cm 3 ) as compared to conventional implants. The proposed designs of FGM implants have the potential to address the complications of conventional implants in high-density bone.